Some molecular and sero – prevalence study of Anaplasma marginale in cattle in Wassit province - Ola Abd-El Hussain Agaar; Ghyda'a Abbas Jassem (Al-Qadisiyah Journal of Veterinary Medicine Sciences, 2015)
The study was designed to investigate the prevalence of bovine anaplasmosis among cattle from various areas in Wassit governorate. The investigation was performed on 184 blood samples collected from suspected cattle including (85) males and (99) females, aged from < 1year to > 2 years. Samples were collected during the period from October 2012 to April 2013, from AL-Kut, AL-hayy, AL-Bashair, AL-Moufaqia and AL-Noamania areas for investigations about the presence of antibodies against Anaplasma parasite by using indirect ELISA test and to determinate the species of genus Anaplasma by using RFLP-PCR technique. The suspected cattle suffering from fever (41°C), severe anemia, pale mucous membrane, progressive emaciation and drop in milk yield. The results of ELISA test showed that the rate of infection was 13.04 %; the rate of infection was different between age groups and was 8 %, 11.25 % and 16.45 % in ages < 1year, 1-2 year and 2 - 3 years respectively. The study revealed that females were given a higher percent of infection 14.14 % than males 11.7 %, and there were no significant differences under p > 0.05 according to age groups and sex. The highest rate of infection was recorded in AL-Kut 17.14 % followed by AL-hayy 14 % and AL-Bashair 10 % and the lowest rate was recorded in AL-Noamania 8.33 % and AL-Moufaqia 5%. The study showed significant differences in the incidence of disease between the studied districts and areas in Wassit governorate under p < 0.05. The most sensitive method for the diagnosis of Anaplasmosis was the method of polymerase chain reaction. The DNA extraction was performed only on 24 blood samples which positive for Anaplasma spp. by ELISA test. The extracted DNA from blood cells were analyzed by PCR and PCR-RFLP technique using primers derived from 16S rRNA gene and restriction endonuclease Bst1107I enzyme which can recognizes the sequence (GTATAC) in corresponding PCR product of A. marginale and cut it in the position 68 and 509, whereas the used restriction enzyme cannot cut the corresponding PCR product of other Aanaplasma spp., and the result was 20 out of 24 was positive for Aanaplasma spp. by PCR and 18 out of 20 was positive for A. marginale.